Penentuan Letak Liang Gua Batu Tunggal Menggunakan Metode Geolistrik Konfigurasi Wenner di Desa Tegalrejo Kotabaru - Dwi Asmaul Husna; Sri Cahyo Wahyono; Simon Sadok Siregar (Jurnal Fisika FLUX, 2019)
Kotabaru Regency has a cast area with an area of 1.777,6303 km2 with a process of dissolving rocks of carbonate that extends to the coast of the Southeast part of the island of Borneo. The study sites are located in the Batu Tunggal cave at coordinates 3o 11 '41.8 "S and 115o 58' 32.9" E which aims to determine the location of the burrow, diameter, and extent of the cave that is still buried using the Wenner Geoelectric Method configuration. Arrange electrode C1 P1, P2 C2 with a distance of 5-meter electrode 3 paths. The results of the measurements on track 1 were found to be the first hole with an average resistivity value of 295,046 Wm at depths of 1.25 to 17.3 meters with an a area of 237.5 m2, the second hole in depth 13.4 - 17.3 meters with a area of 66 m2, the third hole in depth, 9.94 - 17.3 meters with an a area of 55 m2. The second track found the burrow with an average resistivity value of 140.591 Wm in depth of 9.94 - 17.3 meters with an a area of 114 m2. The third track found the burrow with an average resistivity value of 27.651 Wm in depth 14.4 - 17.3 meters with an a area of 55 m2. The cave lane on track 3 is connected to the first hole of track 1 and connects with the hole in part 2.Cave Hole, Geoelectric, Gua Batu Tunggal, Karst